Schusterphotopsis, a new genus of Sphaeropthalminae (Hymenoptera: Mutillidae) from California, with notes on the closely related genera Acrophotopsis Schuster and Dilophotopsis Schuster - Pitts, James P. (Zootaxa, 2003)
A new genus of Mutillidae from southern California, Schusterphotopsis Pitts, is described and illustrated, including the new species Schusterphotopsis barghesti Pitts. The genus can be distinguished from males of other sphaeropthalmine genera by the dilated and deeply emarginated condition of the mandibles, the posterior position and shape of the mesosternal processes, the presence of lateral carinae on the hypopygidium, and the flattened condition of the hypopygidium. A discussion of this new genus’s relationship to Acrophotopsis and Dilophotopsis is given.